Association of sleep duration with socio-economic status and behavioural problems among schoolchildren - TOPUZOĞLU, AHMET; ARMAN, AYŞE; AY, NADİYE PINAR; PERDAHLI FİŞ, NEŞE (WILEY, 2011)
Aim: In this population-based study, we aimed to determine the total sleep duration (TSD), its association with socio-economic status (SES) and behavioural symptoms among schoolchildren. Methods: A cross-sectional study was performed among schoolchildren in Istanbul. A structured questionnaire evaluating the sleep schedule variables was filled out by their parents. SES was determined according to the Turkish SES scale. Results: The mean age of 2669 children was 8.2 +/- 2.4 years, and 51% of the students were girls. The mean TSD was 10.20 +/- 1.04, and the mean bedtime was 21.57 +/- 0.56 (both in hours, minutes +/- SD). Boys tended to go bed later (p = 0.004) and slept less than girls (p = 0.02). The duration of sleep disruptions increased (p < 0.001), whereas TSD decreased with age (p < 0.001). Multiple linear regression revealed that waking time and TSD decreased significantly (p < 0.05) with higher SES among both girls and boys. Sleep fragmentation was associated with habitual snoring, parasomnias, daytime sleepiness and conduct symptoms. Conclusion: Decreased total sleep duration is more prominent in boys, older children and children among higher socio-economic status. Insufficient sleep attributed to shortened total sleep duration by age and higher socio-economic status might have a negative effect on both sleep hygiene and psychological well-being in schoolchildren.
Keywords: Behaviour; Children; Sleep duration; Sleep time; Socio-economic status; SCHOOL-AGE-CHILDREN; PREVALENCE; SYMPTOMS; HYPERACTIVITY; INATTENTION; DISORDERS; AMERICA